And then there were many: insights from the tangled taxonomy of the Antarctic brittle star Ophioplinthus gelida (Echinodermata: Ophiuroidea) - Chester J. Sands; Chester J. Sands; Timothy D. O’Hara; Alice Guzzi; Alice Guzzi; Alice Guzzi; William P. Goodall-Copestake; William P. Goodall-Copestake; Peter Convey; Peter Convey; Peter Convey; Peter Convey; et al. (Frontiers in Marine Science, 2025)
To effectively manage biological assemblages, a sound knowledge of the biodiversity is essential. The Southern Ocean shelf benthic assemblages are typically comprised of species, the names of which are shared across the huge expanse of the region, indicating large population sizes and good connectivity, inferring resilience. This is despite two decades of studies identifying cryptic or unrecognised species in many benthic groups. In this study we examine the common and widespread species Ophioplinthus gelida (Koehler, 1900) and Ophioplinthus martensi (Studer, 1885), both regarded as occurring throughout the Southern Ocean on continental and island shelves. The two species show subtle differences in morphology, despite O. gelida having very plastic character states. Genetic analysis using mitochondrial sequences shows that the two species are part of a radiating clade with ten distinct elements, six of which group as O. gelida and four as O. martensi. Further investigation showed that one of these elements can be attributed to Ophioplinthus carinata (Studer, 1876), not previously identified on the Antarctic shelf, but shown here to be a dominant fraction of the O. “gelida” in our collections. Furthermore, O. “martensi” from its type locality of South Georgia is genetically similar to Ophioplinthus intorta (Lyman, 1878), from Marion Island, but distinct from those collected from the Antarctic shelf, which may then be considered Ophioplinthus inermis (Bell, 1902). A fifth clade of O. martensi collected from waters deeper than 2000 m was not part of this radiation but grouped together with more distantly related Ophioplinthus species. In general, the genus displays a wide range of morphological character states, varying greatly within O. gelida elements, and often shared between species. Several taxa outside of the O. gelida complex may also include unrecognised cryptic species, making reliable field identifications challenging, and greatly increasing the recognised species diversity and regional endemism.